Private provision of elementary education in India: findings of a survey in eight states - Santosh Mehrotra ; Parthasarthi R. Panchamukhi (Compare Vol. 36, No. 4, December 2006, pp. 421-442, 2006)
Private sector growth in education is the new neo-liberal mantra. Based on data generated by a representative sample survey in eight states, six of which account for two-thirds of the children out of school in India, this paper examines the private sector in elementary education in India, and compares its characteristics with government schools. It argues that the majority of private schools at the lower end of a segmented private sector do not contribute to gender and social equity. Despite their better physical facilities their teachers are poorly paid and trained; and although their outcome and process indicators are better than for government schools, they remain unregulated and offer a poor alternative to low quality government schools.